Effects of nonantibiotic growth promoter combinations on growth performance, nutrient utilization, digestive enzymes, intestinal morphology, and cecal microflora of broilers - Li, Zunyan; Zhang, Beibei; Zhu, Weimin; Lin, Yingting; Chen, Jia; Zhu, Fenghua; Guo, Yixuan (PLOS ONE, 2023)
Given the ban on antibiotic growth promoters, the effects of nonantibiotic alternative growth promoter combinations (NAGPCs) on the growth performance, nutrient utilization, digestive enzyme activity, intestinal morphology, and cecal microflora of broilers were evaluated. All birds were fed pellets of two basal diets—starter (0–21 d) and grower (22–42 d)—with either enramycin (ENR) or NAGPC supplemented. 1) control + ENR; 2) control diet (CON, basal diet); 3) control + mannose oligosaccharide (MOS) + mannanase (MAN) + sodium butyrate (SB) (MMS); 4) control + MOS + MAN + Bacillus subtilis (BS) (MMB); 5) control + MOS + fruit oligosaccharide (FOS) + SB (MFS); 6) control + FOS + BS (MFB); 7) control + MOS + FOS + MAN (MFM); 8) control + MOS + BS + phytase (PT) (MBP). ENR, MOS, FOS, SB, MAN, PT, and BS were added at 100, 2,000, 9,000, 1,500, 300, 37, and 500 mg/kg, respectively. The experiment used a completely random block design with six replicates per group: 2400 Ross 308 broilers in the starter phase and 768 in the grower phase. All NAGPCs significantly improved body weight gain (P < 0.01), utilization of dry matter, organic matter, and crude protein (P < 0.05), villus height and villus height/crypt depth in the jejunum and ileum (P < 0.01), and decreased the feed conversion ratio (P < 0.01) at d 21 and 42. MMS, MMB, MFB, and MFM duodenum trypsin, lipase, and amylase activities increased significantly (P < 0.05) at d 21 and 42. On d 21 and 42, MMS, MMB, and MBP increased the abundance of Firmicutes and Bacteroides whereas MMB, MFB, and MBP decreased the abundance of Proteobacteria, compared to ENR and CON. Overall, the NAGPCs were found to have some beneficial effects and may be used as effective antibiotic replacements in broilers.